Secure and private control using semi-homomorphic encryption. (October 2017) - Farokhi, Farhad; Shames, Iman; Batterham, Nathan
Abstract: Networked control systems with encrypted sensors measurements is considered. Semi-homomorphic encryption, specifically the Paillier encryption, is used so that the controller can perform the required computation on the encrypted data. Conditions on the parameters of the encryption technique are provided that guarantee the stability and the performance of the closed-loop system. The results are subsequently extended Laplacian based distributed systems, such as formation-seeking algorithms. It is shown that the problem of figuring out the state measurements of the neighbouring agents of a compromised agent upon using the proposed algorithm is numerically intractable. Highlights: Presented a secure and private framework for networked control systems. The framework relies on the use of semi-homomorphic encryption. Distributed controller are also proved to be secure under the presented framework.